Structural and Thermal Properties of Ultrasound Treated Oil Palm Empty Fruit Bunch (OPEFB) Fiber - Akindoyo, John Olabode; Suriati, Ghazali; Beg, M. D. H. (2015)
:In this study, surface modification of oil palm empty fruit bunch fiber (OPEFB) was carried out through treatment with ultrasound in 2% sodium hydroxide solution. Surface morphology of the fiber was studied by scanning electron microscope (SEM) analysis, and structural changes to the fiber with respect to treatment were investigated through Fourier transforms infrared spectroscopy (FTIR) analysis and X-ray diffraction (XRD) analysis. Furthermore, thermal stability of the treated fiber was investigated through thermogravimetric (TGA) analysis. Morphological changes in form of opened pore spaces and structural changes through disappearance, reduction and shifting of functional group intensities were observed for the fiber after ultrasound treatment as revealed by SEM and FTIR analysis. Density measurement revealed increased density of OPEFB fiber with respect to ultrasound treatment and also increased crystallinity was confirmed by XRD studies. Moreover, thermal stability of the fiber was found to increase after ultrasound treatment.